THE EFFECT OF POSITRONIUM FORMATION IN POSITRON ALKALI-ATOM SCATTERING - Ray, H.; Adhikari, S. K.; Ghosh, A. S. (Elsevier B.V., 1994)
We study e+-Na, e+-K, and e+-Rb scattering using the close coupling approach in the static and coupled static expansion schemes. We calculate partial wave elastic scattering phase shifts and total elastic and Ps formation cross sections up to an incident positron energy of 100 eV. The effect of the positronium formation channel on the elastic channel is found to be strong in all cases up to an incident positron energy of 10 eV. We also make an estimate of the total cross section which exhibits a minimum as a function of energy at low energies.